ENT 530 Social Media Portfolio: The Chief's Restaurant / Muhammad Riza Mohd Shafe'e - Mohd Shafe'e, Muhammad Riza (2021)
As to summarize this report, I can say that the online business I create on the social media platform, Facebook, named The Chief’s Restaurant will be an exceptional and excellent company. I believe my business can strive to be the best restaurant in the world as it is possible to reach my vision or target and carry on my mission. The advertisement I design and post on Facebook will be able to catch the world by the eye and heart. As to briefly introduce the company I chose for this assignment, Social Media Portfolio: Report, I chose to create a restaurant named The Chief’s Restaurant. The Chief’s Restaurant was established at Bukit Antarabangsa, Ampang, Selangor in Malaysia on the month of November 2020. It is a new restaurant dedicated to honour my father, Mohd Shafe’e Ramli, as he is often called as ‘Chief’ by his friends, peers even family members. Even my friends call him Uncle Chief. He is an art enthusiast, majoring in fine arts and is in love with culinary. He loves to cook a lot, mainly western because he used to live in the US for 10 years during his study there. His favourite is Pasta. The very concept and main idea for this restaurant is to combine Arts and Food together to create a masterpiece cooking. As it is well known, there is a saying that states ‘Cooking is an Art’. With this in mind, The Chief’s Restaurant is created with a concept of a restaurant filled with art pieces such as paintings and sculpture. This restaurant is designed that way so that visitors can enjoy their exceptional meal while appreciating the artworks around them. The slogan of the company has the idea of highlighting this by phrasing it into a sentence, “Food is a painting that on a canvas of plates”. This slogan tells that food is a form of art itself.